A rotina da creche comunitária de Fortaleza: tempo de espera e ociosidade - Andrade, Rosimeire Costa de (2002)
The present article is an ethnographic study focused on the waiting and idleness present in the routine of a community day nursere sponsored in Fortaleza. The research was carried out in a day nursere sponsored by the State Governament of Ceará and was based on observation and interviews. The analysis of the data was based on the socio-interactionist theories of development by Vygotsky and Wallon, and the studies of Foucault on disciplina's power. Its results suggest, amongst other things, that: 1)the work done with the children in the nurse's is based on a scholar module, especially a traditional one; 2) the knowledge the teachers have of the children cause the routine to be "natural "; 3) out of the ten hours a day, less than 4% of them are planned; 4) the routine including waiting and idleness, reflects the need to impose discipline on the children for it to function well.